QUALITY OF WORK LIFE OF WOMEN TEACHERS – A study with special reference to College Teachers in Alappuzha District of Kerala State. - Swapna.R
Every successful organization owes its prosperity to an efficient and dedicated workforce. Employees are the real force behind every prosperous institution. Organizations need to focus on providing good working environment to their workers in order to retain them for longer period as well as for the achievement of organizational goals. Quality of Work life(QWL) has emerged as one of the most important aspects of job that ensures long term association of employees with an organization.Quality of work life (QWL) refers to the favorableness or unfavourableness of a job environment for the people working in an organization. According to the American Society of Training and Development Quality of Work Life is a process of work organizations which enable its members at all levels to actively participate in shaping the organizations environment, methods and outcomes. This value based process is aimed towards meeting the twin objectives of enhanced effectiveness of organizations and improved quality of life at work for employees.